2013
DOI: 10.1038/cddis.2013.364
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of high- and low-molecular weight hyaluronan on CXCL12-induced CXCR4 signaling depend on CD44

Abstract: The tumor microenvironment makes a decisive contribution to the development and dissemination of cancer, for example, through extracellular matrix components such as hyaluronan (HA), and through chemokines that regulate tumor cell behavior and angiogenesis. Here we report a molecular link between HA, its receptor CD44 and the chemokine CXCL12 in the regulation of cell motility and angiogenesis. High-molecular-weight HA (hHA) was found to augment CXCL12-induced CXCR4 signaling in both HepG2iso cells and primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 48 publications
1
73
0
5
Order By: Relevance
“…Previous studies have suggested an interaction between hyaluronan-activated CD44 and CXCL12/CXCR4 signaling in induction of leukemia cell and human umbilical endothelial cell-polarization and subsequent migration [63], [73]. Ligand-induced CXCR4 activation promotes angiogenesis via stimulation of endothelial cell migration and proliferation, as well as VEGF production [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested an interaction between hyaluronan-activated CD44 and CXCL12/CXCR4 signaling in induction of leukemia cell and human umbilical endothelial cell-polarization and subsequent migration [63], [73]. Ligand-induced CXCR4 activation promotes angiogenesis via stimulation of endothelial cell migration and proliferation, as well as VEGF production [43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high molecular weight HA (HMW-HA) was reported to be anti-angiogenic [207,208] and immunosuppressive [209]. Despite these evidences, their role in angiogenesis is controversial since LMW-HA was also shown to inhibit angiogenesis impairing the CXC ligand 12 (CXCL12)/CXC Receptor 4 (CXCR4) pathway, as opposed to what observed with HMW-HA [210]. In addition, HMW-HA seems to stimulate angiogenesis cooperating with versican and inducing FGF-2 expression [211].…”
Section: Hyaluronan: Not Only a Mere Gluementioning
confidence: 99%
“…11 The key function of CD44 in growth control and in transformation prompted us to test its potential role as a regulator of the Wnt pathway. CD44 is a major Wnt target in the intestine.…”
mentioning
confidence: 99%